PENGEMBANGAN MEDIA INTERAKTIF ENERGY FUN BERBASIS ANDROID PADA MATERI ENERGI DAN PERUBAHANNYA - Mulia, Parindra Mahardika; Aan Nurfahrudianto; Ika Santia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and describe the feasibility of an interactive learning media based on an Android application called Energy Fun for the topic of energy and its transformations for fourth-grade elementary school students. The background of this research stems from the fact that IPAS (Science and Social Studies Integration) learning is still conventional, where teachers tend to rely on textbooks and worksheets without the support of relevant learning media. Although the school has provided technological facilities such as projectors and laptops, their utilization has not been optimal.This research employs the Research and Development (RnD) method using the 4D development model (Define, Design, Develop, Disseminate). The feasibility validation was conducted by a subject matter expert, media expert, and classroom teacher, while student responses were obtained through questionnaires distributed to 21 fourth-grade students. The validation results showed that Energy Fun obtained an average validity score of 93%, categorized as “very valid”. Meanwhile, student responses reached 94%, categorized as “very good”.These findings indicate that Energy Fun is feasible for use in IPAS learning activities, as it meets the criteria for content and visual validity. Moreover, the media was very well received by students, as reflected in their enthusiasm and active participation during the learning sessions using the Energy Fun application.